Response of Dicamba/Fluroxypyr/Glyphosate-Resistant Kochia to Atrazine and Alternative Postemergence Herbicides - R. Liu; V. Kumar; R. Currie; P. W. Geier; T. Lambert; P. W. Stahlman (Kansas Agricultural Experiment Station Research Reports, 2020)
Two kochia accessions (KS-4A and KS-4H) were previously identified from a corn field near Garden City, KS, with multiple resistance to glyphosate (Roundup PowerMax), dicamba (Clarity), and fluroxypyr (Starane Ultra). The objectives of this research were to (1) determine the response of these kochia accessions to preemergence (PRE) and postemergence (POST) applied atrazine (Aatrex) in dose-response assays, and (2) determine the effectiveness of alternative POST herbicides. Seeds of a known susceptible kochia accession (SUS) collected from research fields in Hays, KS, were used for comparison. Greenhouse experiments were conducted at the Kansas State University Agricultural Research Center near Hays, KS, in a randomized complete block design with 4 to 12 replications. For Aatrex PRE dose-response assay, germination trays (each 10- × 10-inch) containing field soil were used. Fifty seeds from each accession were separately sown on the soil surface in each tray. PRE applied Aatrex doses, including 0, 1/4X, 1/2X, 1X, 2X, and 4X (1X of Aatrex = 32 oz/a) were tested. Emerged kochia seedlings from each tray were counted 28 days after treatment (DAT). For Aatrex POST dose-response assay, kochia plants from SUS and KS-4H accessions were grown in 4- × 4-inch pots containing commercial potting mixture. The same doses of Aatrex (as for PRE dose-response) were tested on 3- to 4-inch tall kochia plants. In a separate greenhouse study, the SUS and KS-4H accessions were also tested with alternative POST herbicides. Data on percent visual control and shoot biomass were collected at 21 DAT in both Aatrex POST and alternative POST herbicide studies. Results indicated that the effective dose (ED50 values) of PRE applied Aatrex required for 50% reduction in seedling emergence of KS-4A, KS-4H, and SUS was 129, 7, and 1 oz/a, respectively, indicating 129- and 7- fold resistance in KS-4A and KS-4H accessions. Furthermore, the KS-4H accession showed 248-fold resistance to POST applied Aatrex, as compared to SUS accession. Among alternative POST herbicide programs, Gramoxone, Huskie, Talinor, and Sharpen alone or with 2,4-D provided excellent control (96-100%) of SUS and KS-4H accession at 21 DAT. In conclusion, these results indicate that dicamba/ fluroxypyr/glyphosate-resistant kochia from Garden City, KS, are also highly resistant to PRE and POST applied atrazine. However, alternative POST herbicides such as Huskie, Talinor, Gramoxone, Sharpen alone, or with 2,4-D were effective control options for this multiple resistant kochia accessions.
Keywords: Atrazine resistance; kochia; multiple herbicide resistance